Five-year outcome after pelvic floor reconstructive surgery: evaluation using dynamic magnetic resonance imaging compared to clinical examination and quality-of-life questionnaire. (October 2018) - Alt, Céline D; Benner, Laura; Mokry, Theresa; Lenz, Florian; Hallscheidt, Peter; Sohn, Christof; Kauczor, Hans-Ulrich; Brocker, Kerstin A
Background: Dynamic magnetic resonance imaging (dMRI) captures the entire pelvis during Valsalva maneuver and helps diagnosing pelvic floor changes after reconstructive surgery. Purpose: To evaluate therapeutic outcome five years after reconstructive surgery using clinical examination, dMRI, and quality-of-life (QOL) questionnaire. Material and Methods: Clinical examination, dMRI, and QOL questionnaire were conducted before surgery and in the follow-ups at 12 weeks, one year, and five years in women with pelvic organ prolapse (POP) stage ≥2. dMRI was performed at 1.5-T using a predefined protocol including sagittal T2-weighted (T2W) sequence at rest and sagittal T2W true-FISP sequence at maximum strain for metric POP measurements (reference points = bladder, cervix, pouch, rectum). Pelvic organ mobility (POM) was defined as the difference of the metric measurement at maximum strain and at rest. Results: Twenty-six women with 104 MRI examinations were available for analysis. dMRI results mostly differ to clinical examination regarding the overall five-year outcome and the posterior compartment in particular. dMRI diagnosed substantially more patients with recurrent or de novo POP in the posterior compartment (n = 17) compared to clinical examination (n = 4). POM after five years aligns to preoperative status except for the bladder. POM reflects best the QOL results regarding defecation disorders. Conclusion: A tendency for recurrent and de novo POP was seen in all diagnostic modalities applied. dMRI objectively visualizes the interaction of the pelvic organs and the pelvic floor after reconstructive surgery and POM correlated best with the women's personal impression on pelvic floor complaints.